2020
DOI: 10.1101/2020.05.10.086678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SurEau.c : a mechanistic model of plant water relations under extreme drought

Abstract: We describe the operating principle of the detailed version of the soil-plant-atmosphere model SurEau that allows, among other things, to predict the risk of hydraulic failure under extreme drought. It is based on the formalization of key physiological processes of plant response to water stress. The hydraulic functioning of the plant is at the core of this model, which focuses on both water flows and water pools using variable hydraulic conductances. The model considers the elementary flow of water from the s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…In order to quantify the relative importance of hydraulic traits in survival of a single plant under extreme droughts, we performed simulations with SurEau.c (Cochard et al, 2020. The code to run the program and the MS EXCEL files can be found in Notes S1). This model computes elementary water flow from the soil to the atmosphere accounting for the resistance and the storage of four plant organs, roots, trunk, branches and leaves.…”
Section: Simulations With the Sureau Modelmentioning
confidence: 99%
“…In order to quantify the relative importance of hydraulic traits in survival of a single plant under extreme droughts, we performed simulations with SurEau.c (Cochard et al, 2020. The code to run the program and the MS EXCEL files can be found in Notes S1). This model computes elementary water flow from the soil to the atmosphere accounting for the resistance and the storage of four plant organs, roots, trunk, branches and leaves.…”
Section: Simulations With the Sureau Modelmentioning
confidence: 99%
“…In a meta‐analysis, Anderegg et al (2016) found that hydraulic vulnerability to embolism and safety margins was the only significant predictor of elevated rates of tree mortality. Hydraulic traits are thus crucial in predicting the response of plants to future environmental extremes related to climate change; this is reflected in recent efforts to incorporate hydraulic traits into process‐based vegetation models (Christoffersen et al, 2016; Cochard et al, 2020; De Kauwe et al, 2020; McDowell et al, 2013). To date, the majority of plant hydraulic research has focused on species from Europe and North America, leaving Australian plant species under‐represented in the global data set despite the fact that Australia is more exposed to the impacts of increasing temperatures and more frequent drought than many other regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…I tested this hypothesis with the mechanistic model SurEau (Martin St-Paul et al 2017, Cochard et al 2020) developed to simulate plant water relations and hydraulic functioning during water stress. My objective is not provide a full description of the model, which is available elsewhere (Cochard et al 2020), but to focus only on the key physiological processes temperaturedependent.…”
Section: Introductionmentioning
confidence: 99%